Strategi Penataan Kawasan Permukiman Kumuh Perkotaan Kampung Bandar Kota Pekanbaru - Ade Masya Resa; Zulfan Saam; Suardi Tarumun (Universitas Riau, 2017)
This study aims to analyze the causes of slum factors and analyze the strategy of slum upgrading in Kampung Bandar. Research has been conducted at Kampung Bandar Slum Area from February 1 February through April 30, 2017. The research method is a desciptive method with descriptive analysis and Analyical Hierarchy Process (AHP) approach. Primary data were collected through observation and AHP questionnaire instrument. Secondary data were obtained from the relevant department of this research. The analysis shows that the slums of Kampung Bandar are caused by there is no legality of spatial plan, low affordability, lack of optimal regulatory enforcement, and inadequate housing infrastructure services. The Strategy of slum updrading at Kampung Bandar are prevention strategies and quality improvement strategies. Preventive strategies consisting of capacity building, supervision and control, and community empowerment. Quality improvement strategies from: rehabilitation, revitalization, and resettlement.